Genetic diversity of kampung chicken (Gallus gallus domesticus) from selected areas in East Coast Peninsular Malaysia inferred from partial control region of mitochondrial DNA - Ha, H.C.; Nguang, S.I.; Zarizal S.; Komilus C.F.; Norshida I.; Ahmad-Syazni K. (Penerbit Universiti Kebangsaan Malaysia, 2017)
After the 2014 Malaysia massive flood, genetic variation of the kampung chicken Gallus gallus domesticus in East Coast Peninsular Malaysia (ECPM) was investigated for a better understanding of their genetic diversity for its conservation. A total of fifty-nine samples were collected from three states; Kelantan, Terengganu and Pahang for mitochondrial DNA analysis. Partial mtDNA control regions were amplified, sequenced, and analyzed to determine the genetic variation among the states. Eleven haplotypes were detected among all the samples. Hap-1 was the most widespread haplotype among the three states and comprised of 45.8% of all samples. Genetic variation was the highest in Pahang (Pi = 0.01037, Hd = 0.8676), followed by Terengganu (Pi = 0.00938, Hd = 0.7316) and Kelantan (Pi = 0.00363, Hd = 0.5579). Low nucleotide diversity in Kelantan indicated the loss of genetic resources, which might be due to the population bottleneck phenomenon. Both the non-significant values of Tajima’s D and Fu’s FS in Pahang and Terengganu, suggested that they were at genetic equilibrium. Significant deviation from Tajima’s D neutrality test (P<0.05) in Kelantan indicated the possibility of population expansion, which might be a result of population recovery from the population bottleneck due to the massive flood in December 2014.